Pengaruh Motivasi dan Kinerja Pegawai Terhadap Kualitas Pelayanan Publik di Kantor Kecamatan Buduran Kabupaten Sidoarjo - Hesty Mulasari; Bambang Suratman (Universitas Negeri Surabaya, 2020)
The study explain the relationship between motivation and employee performance has a positive impact on the quality of public services in the District Office of Buduran in Sidoarjo. The study intends to see the influence of employee motivation and performance positively and significantly on the quality of public services in the District Office of Buduran in Sidoarjo.The focus in this research of the problem in this study is how the influence of employee motivation and performance on the quality of public services in the District Office of Buduran in Sidoarjo. While the research hypothesis of this study is that motivation and performance have a positive and significant influence on the District Office of Buduran of Sidoarjo.The theory used in this research is theory of excellent service, as it relates to quality of service and the satisfaction of the community. Type of this research is quantitative descriptive. Collection of data used technique of questionnaire. The respondents in this study as much as 397 respondents has criteria age 17 and over, and never doing service at the District Office of Buduran of Sidoarjo. Sampling method used proportional random sampling. To test hypothesis used multiple linear regression with the application software Special Package of Statistical Science (SPSS) 22.0.The observation results state that the effect of motivation on the quality of public services is 55,5% so there is a positive and significant relationship between motivation on the quality of public services in the District Office of Buduran of Sidoarjo. The effect of employee performance on the quality of public services is 52,9%, so there is a positive and significant relationship between the performance of employee on the quality of public service in the District Office of Buduran of Sidoarjo. While the relationship of motivation and performance of employee to the quality of public services is 39,8% and the remaining 60,2% is influence by other variables unknown in this study, so there is a positive and significant relationship between motivation and performance of employee to the quality of public services in District Office of Buduran of Sidoarjo.